2002
DOI: 10.1530/eje.0.1470049
|View full text |Cite
|
Sign up to set email alerts
|

A dose titration model for recombinant GH substitution aiming at normal plasma concentrations of IGF-I in hypopituitary adults

Abstract: Objective: To evaluate a dose titration model for recombinant human GH substitution in adult patients with GH deficiency, aiming at normal plasma levels of IGF-I. Design and methods: Eighteen patients participated and a start dose of 0.17 mg GH/day was used except by two men who started with 0.33 mg/day. To demonstrate a clear GH effect the patients were first titrated, with steps of 0.17 mg GH/day every 6 -8 weeks, to IGF-I levels in the upper range of age-adjusted reference values. The GH dose was then reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…However, a study of mice found that over-expression of IGF-I could increase both muscle strength and muscle mass (Barton-Davis et al 1998). Another alternative explanation is that there are metabolic changes at the carbohydrate level, since we have previously reported that insulin and blood glucose levels both increased in patients after GH substitution (Ekman et al 2002). However, we could not find any relationship between changes in IGF-I and insulin or blood glucose in the GHtreated group.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…However, a study of mice found that over-expression of IGF-I could increase both muscle strength and muscle mass (Barton-Davis et al 1998). Another alternative explanation is that there are metabolic changes at the carbohydrate level, since we have previously reported that insulin and blood glucose levels both increased in patients after GH substitution (Ekman et al 2002). However, we could not find any relationship between changes in IGF-I and insulin or blood glucose in the GHtreated group.…”
Section: Discussioncontrasting
confidence: 64%
“…Patients and control subjects both did the same muscle tests on biomechanical output and EMG at baseline and at the last visit in the study. The GH titration procedure is described in detail elsewhere (Ekman et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported that, in contrast to the standard GH replacement dose (SGH) titrated to normalize serum IGF‐I levels, 15–17 fixed administration of a very low GH dose (LGH) (0·1 mg/day) decreased fasting glucose levels and improved insulin sensitivity without modifying body composition in severely GH‐deficient adults 18 . The mechanism/s responsible for the glucose‐lowering effects of the LGH, however, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The waist/hip ratio was not influenced by the age at onset of GHD, severity of hypopituitarism, or gonadal status [15]. There are conflicting reports on the effect; the waist/hip ratio was found to be unchanged [14,18] or decreased in both genders with more pronounced changes in men [15], while no significant difference was found in the sum of skinfold thicknesses during short-term (6-month) replacement [18].…”
Section: Effect Of Gh Replacement Therapy On Body Compositionmentioning
confidence: 92%
“…Men lose more body fat than women [10,15 ± 19] and a similar trend has been seen in the improvement of bone mineral density (BMD) [4,13, 20 ± 27]. GH secretion is also known to depend on the age, but the change of GH sensitivity by age was not proven after short-term administration of GH [14]. On the other hand, the BMD increase was found to be more marked in young than in old patients in the lumbar spine, the femoral neck and in the trochanter regions after long-term GH substitution [27].…”
mentioning
confidence: 99%